Pregnancy and Lactation in a 67-Year-Old Elderly Gravida following Donor Oocyte In Vitro Fertilization - Leila Magistrado; Mary C. Tolcher; Anju Suhag; Sonal Zambare; Kjersti M. Aagaard (Case Reports in Obstetrics and Gynecology)
There is limited data on the anticipated perinatal course among gravidae in their sixth and seventh decades. Our objective was to describe the relatively uncomplicated prenatal, intrapartum, and postpartum course of a 67-year-old essential primigravida. Briefly, our patient conceived a singleton pregnancy via IVF with donor oocytes, then presented at 13 6/7 weeks of gestation to initiate prenatal care. Her medical history was significant for chronic hypertension, hyperlipidemia, and obesity. Her cardiac function was monitored throughout pregnancy, and she delivered at 36 1/7 weeks by cesarean for a decline in left ventricular function with mitral regurgitation. Her intrapartum and postpartum course was uncomplicated, and she was able to successfully breastfeed for six months and resume prepregnancy activity. For comparison, we analyzed deliveries among gravidae>45 years of age from our institutional obstetrical database (2011-2018). This case represents the eldest gravidae identified in the literature and illustrates the potential for a relatively uncomplicated perinatal course with successful lactation. This case may enable other providers to counsel elderly patients on anticipated outcomes inclusive of ability to breastfeed.